E-leave management system and payroll - Chua, Meng Fei (2018)
E-Leave Management System and Payroll (E-LMSP) project is a web application and mobile application which can be used for all the organization or company that will ease the employees leave management. This is due to the problem in using manual system which can cause damage, missing and can be costly as well. In addition, it also will cause delay in leave request when the respective officer not in the office. To solve leave delayed problem, this system provided with the automated function ease leave management process such as information of employees, approval of leave, types of leave, leave balances, payment, notification of email, report generation are element of this system. The system is design in such a simple and friendly user interface to ease the users to use. Every employee is provided with unique username, password and accessible either by an employee or admin for log into a system. Moreover, the functions of administrator for this system are to register the new employee, delete and update information of user in a database. Administrator is known as higher authorities that use to manage the leave whether want to approve or reject the leave of employees. This system also provides the function that help the administrator to auto calculate the salary for each employee based on leave request by employees. This system is developed by using Waterfall method to ensure it is deployed in the prescribed time. As a conclusion, this system is very useful for any companies or organization where there are have large number of employee and easier to track and manage employees leave.